Yield control of chemically-synthesized magnetite nanoparticles - N. K., Devaraj; B. H., Ong; M., Matsumoto (TAYLOR & FRANCIS INC, 2008)
Magnetic Fe3O4 nanoparticles have generated a vast amount of interest as they bridge the gap between the atomic and microscopic world. Below a certain size (< 15 nm), these particles display a novel phenomenon known as superparamagnetism in which they can be magnetized and demagnetized rapidly with the aid of an external magnetic field. Thus, they have potential applications such as targeted drug delivery, hyperthermia, etc. in the biomedical field. Yield control is essential if these particles are to be used for diverse applications on a large scale. In this study, Fe3O4 have been prepared using the standard co-precipitation of Fe2+ and Fe3+ with an alkaline base. Three synthesis parameters, namely the stirring rate, stirring period and the reaction temperature were varied to study their effects on the yield of the nanoparticles.